Evidence for a role of delta sleep-inducing peptide in slow-wave sleep and sleep-related growth hormone release in the rat. - Iyer, K S (1988)
To examine the role of delta sleep-inducing peptide (DSIP) in sleep-related growth hormone (GH) release, male rats were deprived of sleep for 4 hr by placing them on a slowly rotating wheel. Sleep deprivation by this method caused a significant increase in GH release, as indicated by the increase in plasma GH concentrations (P less than 0.01), and also in the amount of slow-wave sleep (SWS) (P less than 0.001) above initial values after removal of the animals from the rotating wheel. These increases were blocked by microinjection into the third cerebral ventricle of highly specific antiserum to DSIP. In control rats receiving an equal volume of normal rabbit serum, the significant increase in plasma GH as well as SWS remained after removal of the rats from the wheel. The increased release of endogenous DSIP in the sleep-deprived animals may have caused an increase in SWS as well as plasma GH. Since DSIP increases plasma GH after its injection into the third cerebral ventricle and since passive immunization against DSIP blocks the increase in SWS and GH release that follows the 4 hr of sleep deprivation, the results suggest that DSIP can be a physiological stimulus for sleep-related GH release as well as for the induction of SWS.